INOVASI TEKNOLOGI DALAM PENGELOLAAN LOGISTIK PEMILU UNTUK MENINGKATKAN EFISIENSI DAN KEPERCAYAAN PUBLIK - Muhammad Ikhsan Irwansyah; M. Rayhan Shafaqa; Farras Haryo Wicaksono; Akhirul Maulidan Yasin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Election logistics management in Indonesia often faces challenges such as delivery delays, uneven distribution, and damaged equipment. This article aims to identify innovations in election logistics management that can enhance efficiency and public trust. Using a qualitative approach through literature studies and in-depth interviews, the study finds that implementing technologies like the Internet of Things (IoT), blockchain, and Geographic Information Systems (GIS) has the potential to improve the effectiveness of election logistics distribution. Additionally, risk management based on the COSO ERM framework demonstrates benefits in reducing uncertainties and increasing distribution reliability. However, challenges related to infrastructure and inter-agency coordination remain barriers that need attention.